2016
DOI: 10.1117/12.2219161
|View full text |Cite
|
Sign up to set email alerts
|

High throughput Jet and Flash Imprint Lithography for semiconductor memory applications

Abstract: Imprint lithography has been shown to be an effective technique for replication of nano-scale features. Jet and Flash* Imprint Lithography (J-FIL*) involves the field-by-field deposition and exposure of a low viscosity resist deposited by jetting technology onto the substrate. The patterned mask is lowered into the fluid which then quickly flows into the relief patterns in the mask by capillary action. Following this filling step, the resist is crosslinked under UV radiation, and then the mask is removed, leav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The results are reported in Figure 11. The newest material enhanced drop spreading by a factor of three relative to the older material [12]. Fig.…”
Section: Jettingmentioning
confidence: 90%
See 1 more Smart Citation
“…The results are reported in Figure 11. The newest material enhanced drop spreading by a factor of three relative to the older material [12]. Fig.…”
Section: Jettingmentioning
confidence: 90%
“…In a recent experiment, resist drop diameter for a 1.0 pL drop was measured for three different substrate cases [12]: 1) Original resist on an adhesion layer 2) Modified resist on the adhesion layer material 3) A newer material combination designed to enhance drop spreading After resist jetting, the drops were exposed to UV light approximately 1 second to cure. The results are reported in Figure 11.…”
Section: Jettingmentioning
confidence: 99%
“…By careful optimization of several parameters (resist drop volume, system controls, material engineering, design for imprint and system controls), fill time can be decreased. It has been reported that throughput per imprint station improved significantly to 15 wafers per hour with a 1.5 s fill time [60]. Now it is targeted at 80 wafers per hour on a four station.…”
Section: Status and Challengesmentioning
confidence: 99%
“…Among the wide variety of NIL technologies, jet and flash imprint (J-FIL) is the most suitable for IC fabrication for which high productivity and high yield are required. [16][17][18] Figure 1 shows the J-FIL process. Resist is selectively applied by an inkjet to an imprinting field whose size is almost the same as that of an exposure field of a conventional optical scanner (∼26 × 33 mm 2 ), and then a patterned mask (template) is directly contacted to the field with UV exposure.…”
Section: Nilmentioning
confidence: 99%